Malondialdehyde (MDA) Ovary and Estradiol Blood Serum Levels of Premenopause White Rat (Rattus norvegicus) after Turmeric Powder (Curcuma longa L.) Treatment - Teguh Suprihatin; Sri Widyarti; Muhaimin Rifa'i; Sri Rahayu (Journal of Tropical Life Science, 2019)
Premenopause is a physiological condition in a female individual that has entered the aging period, a condition usually characterized by elevated MDA levels and decreased estrogen levels. The objective of this study was to determine the level of ovarian MDA and estradiol serum levels of premenopausal white rat blood after oral turmeric powder treatment. The animals used were 30 female Wistar strains white rat, age 12 months with an average body weight 200-250 g. The animals were divided into 6 groups, namely the negative control group (P0) with 4 ml/day distilled water treatment; positive control group (P1), this group was treated with pure curcumin powder 6.75 mg/kg BW; treatment group 1 (P2), group was treated with turmeric powder 100 mg/kg BW; treatment group 2 (P3); treatment group 3 (P4); and treatment group 4 (P5), these group were treated with turmeric powder at 200 mg/kg BW; 400 mg/kg BW; and 800 mg/kg BW dose respectively. Oral Treatment was administered daily for 27 days. Blood collection was performed on days 0, 14, and 28. The ovarian collection was conducted on day 28. MDA ovarian level was measured using TBA method and blood serum estradiol level was measured using ELISA method. The results exhibited that the positive control group (P1) and the treatment group (P2-P5) showed significantly lower ovarian MDA levels compared with the negative control group (P0). The turmeric powder dose 200 mg/kg BW (P3) can increase estradiol levels by day 14 (3.32 Â± 0.26 Ïg/mL) and at day 28 (4.01 Â± 0.26 Ïg/mL).